Deve kuşlarından izole edilen ishal etkenleri - Borum, A. Ebru (My University, 2017)
Bu çalışmada ishalli devekuşlarından alınan fekal svaplardan etken izolasyonu yapmak amaçlandı. Toplam 42 ishalli deve kuşundan fekal örnekler alındı. Örneklerden 38 (%90,47) tanesi saf kültür, 4 (%9,52) karışık kültür olarak üredi. İzole edilen etkenler, 26 (%61,9) Escherichia coli, 14 (%33,33) Campylobacter jejuni, 4 (%9,52) Aeromonas hydrophila, 2 (%4,76) Aeromonas sobria olarak belirlendi.

In this study, it was aimed to isolate microorganisms from the fecal swab specimens from ostriches with diarrhea. A total of 42 fecal samples were collected from ostriches with diarrhea. The organisms were isolated in pure culture from 38 (90.47%) samples and were isolated in mixed culture from 4 (9.52%) samples. A total of 4 strains were isolated from the 42 fecal samples. Of the strains isolated, 26 (61.9%) were identified as Escherichia coli, 14 (33.33%) as Campylobacter jejuni, 4 (9.52%) as Aeromonas hydrophila, 2 (4.76%) as Aeromonas sobria.
Isolation of agents of diarrhea in ostriches
Keywords: Devekuşu; Dışkı Svap; İshal; Ostriches; Fecal Swab; Diarrhea; Deve; Kuş; Bird; Camel